Assessment of Resources for Story Hour Programs: Review of Public Libraries in Anambra State, Nigeria - Osuchukwu, Ngozi P. (Qualitative and Quantitative Methods in Libraries, 2017)
Regular assessment enables the library to improve its resources in order to meet the needs of the users. A survey was conducted to assess the library resources for effective story hour programs in public libraries in Anambra state, Nigeria. Questionnaires, observation checklist and oral interview were used in data collection. Data were analyzed using frequency counts and percentages. The results show among other things, the overwhelming difference between the availability of print and total absence of audiovisual resources in almost all the libraries (90.9%). Recommendations made include encouraging regular assessment and provision of relevant resources.